Rich languages from poor inputs - Piattelli-Palmarini, Massimo; Berwick, Robert C. (Oxford : Oxford University Press, 2013)
This text addresses one of the most famous and controversial arguments in the study of language and mind, the Poverty of the Stimulus. Internationally recognised scholars consider afresh the issues surrounding this argument and discuss its relation to the process of language acquisition.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Language acquisition; Language acquisition -- Social aspects